Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Nest exposure to marine flooding and impacts on green turtle (Chelonia mydas) embryos under rapid sea level rise: The role of beach geomorphology and hydrodynamics - Sophie Morisseau; Matthieu Jeanson; Aline Aubry; Lucas le Gall; Cyrielle Delvenne; Sarah Charroux; Yann Mercky; Charles Le Bozec; Marc Girondot; Damien Chevallier; Elliott Sucré (Marine Environmental Research, 2025)

Environmental preferences of green sea turtles (Chelonia mydas) for egg-laying on a fringing reef pocket beach, Mayotte Island - Sophie Morisseau; Matthieu Jeanson; Sarah Charroux; Yann Mercky; Charles Le Bozec; Michel Charpentier; Lucas Le Gall; Cyrielle Delvenne; Marc Girondot; Elliott Sucré; Damien Chevallier (Frontiers in Marine Science, 2025)
Understanding the spatial ecology of sea turtles is essential to ensure their long-term conservation by the preservation of their environment. The distribution and environmental preferences for egg-laying by the green turtle ( Chelonia mydas ) were studied on Grande Saziley beach in Mayotte (north of the Mozambique Channel). Green turtle nesting activity was geolocated during night patrols and the depth of specific nests was measured during two field campaigns in 2021 and 2022. Various original environmental parameters related to vegetation and beach morphology were extracted in a GIS environment based on this geolocated data using orthophotography and digital elevation models (DEMs) created by drones prior to field deployments. Sediment samples were also collected from the beach. Thanks to the combination of fieldwork and GIS analysis, this study makes it possible to examine a set of variables, which until now have rarely been studied simultaneously. The results showed that the Grande Saziley beach is a heterogeneous site with the distribution of egg-laying being concentrated in two hotspots. After principal component and GLMM statistical analysis, it appeared that gravid females preferentially lay in a low proportion of coarse sand at the bottom of the nest, at higher elevation and predominantly in surface sand with a low calcium carbonate content. This preference seems to be linked more to elevation, where black sand is mainly found at the top of the beach, rather than an intentional choice based on sand composition. No significant egg-laying site-related variables were found to explain the variations in nest depth. Our study was based on a new approach combining GIS techniques and drone surveys, enabling the collection of environmental parameters, a methodology that can easily be reproduced on other nesting beaches, reducing field workload. However, this work should be continued to assess the viability of sites for clutch survival while considering the spatial and temporal heterogeneity of the environment.

Summer predictions of Arctic sea ice edge in multi-model seasonal re-forecasts - Lauriane Batté; Ilona Välisuo; Matthieu Chevallier; Juan C. Acosta Navarro; Pablo Ortega; Doug Smith (Climate Dynamics, 2020)

Polar Ocean Observations: A Critical Gap in the Observing System and Its Effect on Environmental Predictions From Hours to a Season - Gregory C. Smith; Richard Allard; Marcel Babin; Laurent Bertino; Matthieu Chevallier; Gary Corlett; Julia Crout; Fraser Davidson; Bruno Delille; Sarah T. Gille; David Hebert; Patrick Hyder; et al. (Frontiers in Marine Science, 2019)

Ocean Reanalyses: Recent Advances and Unsolved Challenges - Andrea Storto; Aida Alvera-Azcárate; Magdalena A. Balmaseda; Alexander Barth; Matthieu Chevallier; Francois Counillon; Catia M. Domingues; Marie Drevillon; Yann Drillet; Gaël Forget; Gilles Garric; Keith Haines; et al. (Frontiers in Marine Science, 2019)

Observational Needs for Improving Ocean and Coupled Reanalysis, S2S Prediction, and Decadal Prediction - Stephen G. Penny; Santha Akella; Magdalena A. Balmaseda; Philip Browne; James A. Carton; Matthieu Chevallier; Francois Counillon; Catia Domingues; Sergey Frolov; Patrick Heimbach; Patrick Hogan; Ibrahim Hoteit; et al. (Frontiers in Marine Science, 2019)

An assessment of regional sea ice predictability in the Arctic ocean - Rubén Cruz-García; Virginie Guemas; Matthieu Chevallier; François Massonnet (Climate Dynamics, 2019)

An assessment of ten ocean reanalyses in the polar regions - Petteri Uotila; Hugues Goosse; Keith Haines; Matthieu Chevallier; Antoine Barthélemy; Clément Bricaud; Jim Carton; Neven Fučkar; Gilles Garric; Doroteaciro Iovino; Frank Kauker; Meri Korhonen; et al. (Climate Dynamics, 2019)

A Decision Support Tool Facilitating Medicine Design for Optimal Acceptability in The Older Population - Thibault Vallet; Emilie Belissa; Sandra Laribe-Caget; Alain Chevallier; François-Xavier Chedhomme; Patrick Leglise; Matthieu Piccoli; Hugues Michelon; Vanessa Bloch; Sylvie Meaume; Anne-Sophie Grancher; Nathalie Bachalat; et al. (Pharmaceutical Research, 2018)

Erratum to: Intercomparison of the Arctic sea ice cover in global ocean–sea ice reanalyses from the ORA-IP project - Matthieu Chevallier; Gregory C. Smith; Frédéric Dupont; Jean-François Lemieux; Gael Forget; Yosuke Fujii; Fabrice Hernandez; Rym Msadek; K. Andrew Peterson; Andrea Storto; Takahiro Toyoda; Maria Valdivieso; et al. (Climate Dynamics, 2017)

Intercomparison of the Arctic sea ice cover in global ocean–sea ice reanalyses from the ORA-IP project - Matthieu Chevallier; Gregory C. Smith; Frédéric Dupont; Jean-François Lemieux; Gael Forget; Yosuke Fujii; Fabrice Hernandez; Rym Msadek; K. Andrew Peterson; Andrea Storto; Takahiro Toyoda; Maria Valdivieso; et al. (Climate Dynamics, 2017)

Interannual predictability of Arctic sea ice in a global climate model: regional contrasts and temporal evolution - Agathe Germe; Matthieu Chevallier; David Salas y Mélia; Emilia Sanchez-Gomez; Christophe Cassou (Climate Dynamics, 2014)